2020
DOI: 10.31235/osf.io/xpqrs
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrating Ethical Values into Fraud Triangle Theory in Assessing Employee Fraud: Evidence from the Malaysian Banking Industry

Abstract: This study attempts to integrate ethical values into the fraud triangle theory in the context of Malaysian banking industry. Primary data were collected through the survey of 108 questionnaires administered to the employees of the top three largest banks in Malaysia. The findings revealed that ethical values were negatively related to employee fraud, and two elements of fraud triangle theory, namely, opportunity and rationalization, were positively related to employee fraud. This implies that high ethical valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Albrecht et al (2010) also found evidence, in their analysis of fraud cases in South Korea's four largest Chaebols, suggesting that all three elements of the fraud triangle can predict fraud. Said et al (2017) investigated bank employee fraud using a survey of employees at the top three Malaysian banks. The results showed opportunity and rationalization to be positively related with fraud, with rationalization being the strongest influence.…”
Section: Empirical Applications Of the Fraud Triangle In Accounting A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Albrecht et al (2010) also found evidence, in their analysis of fraud cases in South Korea's four largest Chaebols, suggesting that all three elements of the fraud triangle can predict fraud. Said et al (2017) investigated bank employee fraud using a survey of employees at the top three Malaysian banks. The results showed opportunity and rationalization to be positively related with fraud, with rationalization being the strongest influence.…”
Section: Empirical Applications Of the Fraud Triangle In Accounting A...mentioning
confidence: 99%
“…Said et al. (2017) investigated bank employee fraud using a survey of employees at the top three Malaysian banks. The results showed opportunity and rationalization to be positively related with fraud, with rationalization being the strongest influence.…”
Section: Theoretical Underpinning: the Fraud Theory (Tft)mentioning
confidence: 99%
“…This concept argues that perpetrators of unethical behavior devise a rationale for certain morally acceptable behaviors before engaging in fraud or other forms of unethical behavior. Rationalization seeks to justify unethical behavior different from normal criminal activity (Said, Alam, Ramli, & Rafidi, 2017).…”
Section: Rationalizationmentioning
confidence: 99%
“…In order to curb further improper and unethical practices, some insurance associations have drawn up certain procedures and rules to be adhered by the member companies and their agents. Previous research has been conducted on ethical decision-making for banking industry (Said, Alam, Ramli, & Rafidi, 2017). In view of these development, it is the purpose of this research to study the factors contributing to existence of unethical practices in the insurance industry.…”
Section: Introductionmentioning
confidence: 99%